ACCOUNTING FUNDAMENTALS AND VARIATIONS OF STOCK PRICE: METHODOLOGICAL REFINEMENT WITH RECURSIVE SIMULTANEOUS MODEL - Sumiyana Sumiyana; Zaki Baridwan (Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
This study investigates association between accounting fundamentals and variations of stock prices using recursive simultaneous equation model. The accounting fundamentals consist of earnings yield, book value, profitability, growth opportunities and discount rate. The prior single relationships model has been investigated by Chen and Zhang (2007), Sumiyana (2011) and Sumiyana et al. (2010). They assume that all accounting fundamentals associate direct-linearly to the stock returns. This study assembles that all accounting fundamentals should associate recursively.This study reconstructs the model and found that only the first two factors could influence stock returns directly, while the three remaining factors should relate precedently to the earnings yield and book value. This study suggests that new reconstructed relationships among accounting fundamentals could decompose association degree between them and the movements of stock prices. Finally, this study concludes that this methodological refinement would improve the ability of predicting stock prices and reduce stock price deviations. It implies that accounting fundamentals actually have higher value relevance in the new recursive simultaneous equation model than that in single equation model. It also entails that relationship decompositions revitalize the integration of the adaptation and the recursion theories.